Movement pattern definitions for resistance training behavior measurement in diabetes - Brown, Elise C.; Kilgore, Lon J.; Pierce, Kyle; Knox, Allan; Haworth, Joshua L. (Frontiers in Clinical Diabetes and Healthcare, 2024)
Type 2 diabetes can result in debilitating vascular complications, and resistance training (RT) is an effective therapy for improving cardiovascular outcomes. However, only 10–30% of adults meet the public health guidance for RT. While current RT guidelines focus on targeting major muscle groups, guidance specific to simplified movement categorization may augment understanding of RT programming and improve uptake and outcomes. Current movement pattern definitions and descriptions lack clarity, accuracy, and consistency. This paper proposes movement definitions and descriptions to be used for RT intervention design and prescription, and includes the following categories: hip, knee, ankle, vertebral column, vertical push, horizontal push, vertical pull, and horizontal pull. These categories are intended to aid clinicians, researchers, and trainers in RT surveillance and RT intervention design for improving vascular complications in type 2 diabetes. Simplified RT program design using these categories may also facilitate greater RT program understanding and adherence for patients.